2019
DOI: 10.1097/md.0000000000017313
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms of Toll-like receptor-4 and of autophagy-related gene 16 like-1 gene for predisposition of premature delivery

Abstract: To investigate the impact of carriage of single nucleotide polymorphisms (SNPs) of the Toll-like receptor-4 (TLR4) and of autophagy-related gene 16-like-1 (ATG16L1) in preterm delivery (PTD).A prospective cohort of 145 pregnant women was studied. Women were prospectively followed-up until delivery. Genotyping for rs4986790 (Asp299Gly transition) and rs4986791 (Thr399Ile transition) of TLR4 and for rs2241880 of ATG16L1 was done by PCR-restriction fragment length polymorphism. The primary study endpoint was the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Withdrawal of P4 signaling, myometrial activation, fetal signals, and a switch in maternal immune phenotypes from tolerance to inflammation all contribute to the activation of the main inflammatory pathway. In the case of preterm birth, studies in mice show that various perturbations in this inflammatory pathway can occur, leading to premature activation of essential pathways components, resulting in preterm labor polymorphisms (SNPs) in the TLR4 gene are associated with early preterm delivery before gestational week 32 [96]. Downstream of TLR4 and its coreceptor CD14 is MyD88dependent and independent (TRIF-dependent) signaling pathways, that each control specific inflammatory gene expression.…”
Section: Inflammatory Signaling Pathways In Term and Preterm Labormentioning
confidence: 99%
See 1 more Smart Citation
“…Withdrawal of P4 signaling, myometrial activation, fetal signals, and a switch in maternal immune phenotypes from tolerance to inflammation all contribute to the activation of the main inflammatory pathway. In the case of preterm birth, studies in mice show that various perturbations in this inflammatory pathway can occur, leading to premature activation of essential pathways components, resulting in preterm labor polymorphisms (SNPs) in the TLR4 gene are associated with early preterm delivery before gestational week 32 [96]. Downstream of TLR4 and its coreceptor CD14 is MyD88dependent and independent (TRIF-dependent) signaling pathways, that each control specific inflammatory gene expression.…”
Section: Inflammatory Signaling Pathways In Term and Preterm Labormentioning
confidence: 99%
“…Recently, TLR4 expression by decidual endothelial cells, and not immune cells, was identified to be a key for initiating this response, since mice with endothelial-specific TLR4 deletion are resistant to LPS-induced PTB [ 84 ]. In humans, maternal single nucleotide polymorphisms (SNPs) in the TLR4 gene are associated with early preterm delivery before gestational week 32 [ 96 ]. Downstream of TLR4 and its coreceptor CD14 is MyD88-dependent and independent (TRIF-dependent) signaling pathways, that each control specific inflammatory gene expression.…”
Section: Inflammatory Signaling Pathways In Term and Preterm Labormentioning
confidence: 99%
“…38,39 In addition, the majority of the literature contains candidate gene studies that showed 25 additional preterm birth-associated loci that did not reach genome-wide significance level, including AKAP10, ATG16L1, DNMT3B, FLT1, FNDC5, FSHR, IL10, IL16, IL1B, IL1R2, IL4, LEPR, LIFR-AS1, MMP1, MMP2, OGG1, PER3, PGR, PLA2G4D, PRKCA, RLN2, SKA2, TIMP2, TLR4, and VDR. [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56] Of these, rs1800872 in IL10 has notably been associated with various preterm birth outcomes in multiple studies with different sample populations: specifically, with preterm labor associated with preterm premature rupture of membranes at 26 to 34 weeks of gestation in Zaporizhzhia women, with preterm birth at 24 to 37 weeks in Korean women, and with preterm birth before 37 weeks in Indian women. 43,54,56 Medical History ►Fig.…”
Section: Geneticsmentioning
confidence: 99%